PENGARUH PAPARAN KEBISINGAN WEAVING MACHINE TERHADAP RESIKO TERJADINYA HEARING IMPAREMENT PADA KARYAWAN PT. KECUBUNG MOJOGEDANG - Jamil, Nur Khotimah; Sudarman, Sudarman; Putri, Anggi Resina (Medical Journal of Nusantara, 2023)
Noise-induced hearing loss is a sensorineural type of hearing loss caused by exposure to loud enough noise over a long period of time. Hearing loss due to noise has an impact on life. The diagnosis of noise-induced hearing loss was obtained from a hearing examination, pure tone audiometry and audiometric examination results. The impact of noise-induced hearing loss is in several aspects, namely functional, social and emotional aspects, as well as economic aspects. This study aims to determine the effect of the duration of exposure to weaving machine noise on the risk of hearing imparement on employees of PT. Kecubung Mojogedang. This research is a quantitative research using a cross sectional design. The sampling technique is Total Sampling. The sample used was 40 people. The data collected will be analyzed by univariate and bivariate, the data analysis technique in this study uses the contingency coefficient test. The results of the bivariate analysis using the Contingency C coefficient test obtained a value of 0.367 with a significance (p) of 0.013. The significance value (p) is smaller than = 0.05, meaning that Ho is rejected and Ha is accepted, which means that there is an effect of the duration of noise exposure with the risk of hearing loss in employees who work at PT. Kecubung Mojogedang